Nutrient dynamics at Matapouri Estuary, Northern New Zealand - Soliman, Nabil Zaki Gadalla (Auckland University of Technology, 2004)
Mangrove forests are an integral part of coastal wetlands in temperate and tropical regions of the world, including New Zealand. These coastal plants act as a shelter, feeding and breeding grounds for marine and terrestrial organisms. Many overseas studies have investigated the importance of mangrove and seagrass habitats in sustaining coastal food chains. In New Zealand, however, only a few studies have addressed the ecology and food web dynamics of these temperate ecosystems. As a first step to investigate the nutrient dynamics of estuarine food webs in temperate estuaries, this study aimed to quantify the nutrient concentrations in the catchment and the estuary of Matapouri, northern New Zealand. Field studies involved the collection of surface fresh and estuarine water (during low and high tides). Plant material (mangrove and seagrass), and sediment samples were collected at various sites within the estuary. Chemical analyses were carried out to determine the concentration of C, N, P and Si macronutrients and Fe and Zn micronutrients during different seasonal rainfall events. The results suggest that mangrove habitats may act as a source of POC, but not DOC for the adjacent aquatic habitats (i.e., seagrass, sand flats, channels), while seasgrass beds contribute more N to the estuarine system than the mangrove forests. The concentrations of N and P nutrients are strongly influenced by both the freshwater inputs and the bio-chemical processes within the estuary. The results obtained point to the freshwater streams as the main source of Si and Fe in the estuary. However, Zn was higher in the estuarine water compared to the catchment freshwater. NO3 -, NH4+, Fe and Zn concentrations showed strong responses to the higher rainfall months reaching their highest level during the winter and early spring seasons. Conversely, P concentrations showed a negative seasonal pattern, which was linked to monthly rainfall events. Mangrove sediments may operate as a sink for the heavy metal Zn in Matapouri estuary. Iron concentration in seagrass leaves exceeded that in mangrove leaves by 65 orders of. magnitude. The study suggests that seagrass plants could be used as a biological indicator of iron concentration in the estuary. The complex dynamics of bio-chemical cycles in Matapouri indicate that each habitat within the estuary has specific nutrient contributions to the estuarine food web system. However, the catchment and oceanic influences must also be considered in the nutrient balance of these coastal environments.
Keywords: Mangrove swamps -- New Zealand; Mangrove plants -- New Zealand; Mangrove ecology -- New Zealand; Estuarine ecology -- New Zealand